Meta‐analysis of time to extrusion of tympanostomy tubes by tympanic membrane quadrant. (6th August 2021) - Ungar, Omer J.; Baris, Harel; Oron, Yahav; Shilo, Shahaf; Handzel, Ophir; Warshavsky, Anton; Horowitz, Gilad; Abu Eta, Rani; Muhanna, Nidal; Carmel Neiderman, Narin N.
Abstract: Objectives: To investigate the published time to extrusion of tympanostomy tubes inserted in the various quadrants of the tympanic membrane. Methods: Publications were selected by a search with 'PubMed', 'Embase' and 'Web of Science'. A meta‐analysis of time to extrusion as a function of tympanic membrane quadrant intubation was performed. Design, Setting, Participant‐Not relevant Main Outcome Measured: Extrusion rate of tympanostomy tubes inserted in the various quadrants of the tympanic membrane. Results: Eleven studies describing 2232 tympanostomy tubes were enrolled into the quantitative meta‐analysis. The extrusion rate was evaluated at 3‐month intervals up to 24 months post‐intubation, and it did not differ significantly at any of the time points tested for the superior and inferior anterior quadrants. The cumulative extrusion rates were as follows: 11 and 9%, 32 and 23%, 59 and 36%, 80 and 67%, 87 and 70%, 88 and 82%, and 96 and 89% in the superior and anterior quadrants, respectively, at 3, 6, 9, 15, 18, 21 and 24 months post‐intubation, respectively. Conclusion: Time to extrusion of tympanostomy tubes are similar for all 3 tympanic membrane quadrants. The anterior superior quadrant intubation has no superiority in terms of intubation time.